Challenges of the Internationalization of Educational Inspection - Quiroga Fernández, Francisco José (Avances en Supervisión Educativa, 2026)
Building on the discussion forum that emerged from the training session held at the Beatriz Galindo Secondary School in Madrid on 20 November 2025, this analysis aims to draw conclusions that will enable the dissemination of proposals for improvement, thereby contributing to the effective implementation of the opportunities this field offers to the Education Inspectorate. The internationalisation of the Education Inspectorate represents not only a professional innovation but also an outward-looking initiative that results in the improvement of systemic educational quality; consequently, this article concludes with a series of proposals that should be integrated into a comprehensive strategy to promote the Inspectorate’s participation in the internationalisation of education.